2016
DOI: 10.1186/s13063-016-1388-z
|View full text |Cite
|
Sign up to set email alerts
|

Danish study of Non-Invasive testing in Coronary Artery Disease (Dan-NICAD): study protocol for a randomised controlled trial

Abstract: BackgroundCoronary computed tomography angiography (CCTA) is an established method for ruling out coronary artery disease (CAD). Most patients referred for CCTA do not have CAD and only approximately 20–30 % of patients are subsequently referred to further testing by invasive coronary angiography (ICA) or non-invasive perfusion evaluation due to suspected obstructive CAD. In cases with severe calcifications, a discrepancy between CCTA and ICA often occurs, leading to the well-described, low-diagnostic specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…This is a pre-planned substudy and the design of the main Dan-NICAD study was previously published [14]. In short, CCTA is the preferred first-line test in patients with stable chest pain in Denmark.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a pre-planned substudy and the design of the main Dan-NICAD study was previously published [14]. In short, CCTA is the preferred first-line test in patients with stable chest pain in Denmark.…”
Section: Methodsmentioning
confidence: 99%
“…For CMR, an abnormal scan was defined as subendocardial or transmural changes by stress imaging or irreversible defects in ≥ 2 contiguous segments by late gadolinium enhancement imaging. Full description of MPS and CMR analysis was reported in the Dan-NICAD papers [14,15]. CMR core-lab readings were performed in an experienced core lab (William Harvey Research Institute, Queen Mary University of London, London, UK) while MPS Images were analyzed by a different independent core lab (Department of Nuclear Medicine, Aarhus University Hospital, Aarhus, Denmark).…”
Section: Non-invasive Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dan-NICAD study [2] is a cross-sectional trial that included 1675 patients who were referred to coronary computed tomography angiography (CCTA) due to symptoms suggestive of coronary artery disease (CAD). These patients had no previous history of CAD, or advanced AV-block.…”
Section: Methodsmentioning
confidence: 99%
“…Phonocardiography recordings were pooled from three different studies: AdoptCAD [5], BIO-CAC (NCT02913144), and Dan-NICAD [6,7] as shown in Table 1. Only one recording for each subject was included; in cases where more than one recording were available, the first recording was selected.…”
Section: Datamentioning
confidence: 99%